Centrifugal separation experimentation and optimum predictive model development for copper recovery from waste copper smelter dust. Issue 1 (1st January 2018) - Okanigbe, Daniel; Olawale, Popoola; Popoola, Abimbola; Abraham, Adeleke; Michael, Ayomoh; Andrei, Kolesnikov
Abstract: This research has presented a three level-two factors full factorial experimental design that investigated the process parameterization of a centrifugal concentrator for the separation of a waste copper smelter dust (CSD). This was followed by a theoretical contribution involving the development of a scheme of predictive models premised on the concept of constrained interpolant models. These were used for the experimental trend, pattern investigation and furthermore to provide expressions that depicts optimal experimental conditions in this research. Based on the experimental outputs, it was observed that a maximum grade of about 35.02 wt% Cu was achieved at a Rotational Bowl Speed of 120G, Water Flow Rate of 3.0l/min and constant experimental flow rate of 1.48l/min with a Liquid to Solid Ratio of 0.5. Similarly, a minimum output of 14.58% SiO2 and 10.29% Al2 O3 was achieved at same experimental conditions. This clearly depicts a trend geared towards optimum experimental conditions aimed at maximizing Cu output and minimizing SiO2 and Al2 O3 impurities. The predicted outputs premised on the use of Matlab software are in good conformance with the experimental outputs with a high degree of accuracy and confidence level over 97% as shown in Table 1 and corresponding Figures.